Moditva in India: a threat to inclusive growth and democracy. Issue 3 (2nd July 2016) - Tharamangalam, Joseph
ABSTRACT: This article examines the model of development and democracy in India under Narendra Modi's leadership, since May 2014. Three ingredients of the model – a hard-line, pro-business economic policy promising rapid growth; authoritarian governance (purportedly for effective action); and a Hindu nationalist ideology – are assessed in theory and in practice. After considering both the development experience of Gujarat state under Modi (before 2014) and the Modi government's record since assuming power in Delhi, this article argues that the Modi model poses serious threats to inclusive and sustainable growth, hard-won social programmes, human and environmental rights and India's multi-religious and pluralist democracy, regardless of the growth it might deliver.